2012
DOI: 10.1080/00207594.2011.632009
|View full text |Cite
|
Sign up to set email alerts
|

Does gratitude always work? Ambivalence over emotional expression inhibits the beneficial effect of gratitude on well‐being

Abstract: The psychological benefit of gratitude has been well demonstrated in previous studies. However, when we examined these studies closely, we found that the moderators were rarely investigated, suggesting that further work is needed to explore the boundaries of gratitude In this regard, the authors have proposed that ambivalence over emotional expression might be a potential moderator that would inhibit the beneficial effect of gratitude on well-being. Two studies were conducted to examine our hypothesis. Study 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
1
35
0
1
Order By: Relevance
“…This incongruent behavior or interpretation will undermine interpersonal interaction and thus may weaken the mechanisms evoked by gratitude that lead to greater well-being. Indeed, Chen et al (2012) found that the impact of gratitude on well-being is weaker among individuals with higher ambivalence over emotional expression than those are low in such characteristic.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This incongruent behavior or interpretation will undermine interpersonal interaction and thus may weaken the mechanisms evoked by gratitude that lead to greater well-being. Indeed, Chen et al (2012) found that the impact of gratitude on well-being is weaker among individuals with higher ambivalence over emotional expression than those are low in such characteristic.…”
mentioning
confidence: 99%
“…Several studies have supported this idea. For example, Chen, Chen, and Tsai (2012) found that in those college students who possess high ambivalence over emotional expression, the positive relationship between gratitude and happiness was inhibited. This finding indicates that not all individuals can benefit from gratitude to enhance their well-being.…”
mentioning
confidence: 99%
See 3 more Smart Citations